Growth control: a saga of cell walls, ROS, and peptide receptors - Wolf, Sebastian; Höfte, Herman (The plant cell, 2014)
Despite an increasingly detailed understanding of endogenous and environmental growth-controlling signals and their signaling networks, little is known on how these networks are integrated with the cell expansion machinery. Members of the CrRLK1L family control cell wall properties and cell expansion in a variety of developmental and environmental contexts. Two recent reports provide exciting new insights into the mode of action of these RLKs. One study shows that one family member, FERONIA (FER), is required for the production of hydroxyl radicals in the female gametophyte, which causes pollen tube rupture and sperm cell release during fertilization. Another study shows that FER is a receptor for a signaling peptide (Rapid Alkalinization Factor 1 [RALF1]) that triggers cell wall alkalinization and growth arrest, possibly through the inhibition of plasma membrane H+-ATPase activity. RALF1 belongs to a large gene family, with a wide range of expression patterns. Other CrRLK1L family members therefore may also be receptors for RALF-like peptides. These findings have important implications for our understanding of the control of cell wall integrity during growth and raise new intriguing questions.